Towards a bioengineered uterus: bioactive sheep uterus scaffolds are effectively recellularized by enzymatic preconditioning - Padma, Arvind Manikantan; Carrière, Laura; Krokström Karlsson, Frida; Sehic, Edina; Bandstein, Sara; Tiemann, Tom Tristan; Oltean, Mihai; Song, Min Jong; Brännström, Mats; Hellström, Mats (npj regenerative medicine, 2021)
Uterine factor infertility was considered incurable until recently when we reported the first successful live birth after uterus transplantation. However, risky donor surgery and immunosuppressive therapy are factors that may be avoided with bioengineering. For example, transplanted recellularized constructs derived from decellularized tissue restored fertility in rodent models and mandate translational studies. In this study, we decellularized whole sheep uterus with three different protocols using 0.5% sodium dodecyl sulfate, 2% sodium deoxycholate (SDC) or 2% SDC, and 1% Triton X-100. Scaffolds were then assessed for bioactivity using the dorsal root ganglion and chorioallantoic membrane assays, and we found that all the uterus scaffolds exhibited growth factor activity that promoted neurogenesis and angiogenesis. Extensive recellularization optimization was conducted using multipotent sheep fetal stem cells and we report results from the following three in vitro conditions; (a) standard cell culturing conditions, (b) constructs cultured in transwells, and (c) scaffolds preconditioned with matrix metalloproteinase 2 and 9. The recellularization efficiency was improved short-term when transwells were used compared with standard culturing conditions. However, the recellularization efficiency in scaffolds preconditioned with matrix metalloproteinases was 200-300% better than the other strategies evaluated herein, independent of decellularization protocol. Hence, a major recellularization hurdle has been overcome with the improved recellularization strategies and in vitro platforms described herein. These results are an important milestone and should facilitate the production of large bioengineered grafts suitable for future in vivo applications in the sheep, which is an essential step before considering these principles in a clinical setting.